2021
DOI: 10.1002/cbdv.202100058
|View full text |Cite
|
Sign up to set email alerts
|

Supercritical Carbon Dioxide Extraction of Allium ursinum: Impact of Temperature and Pressure on the Extracts Chemical Profile

Abstract: The aim of this study was to extract Allium ursinum L. for the first time by supercritical carbon dioxide (SC−CO2) as green sustainable method. The impact of temperature in the range from 40 to 60 °C and pressure between 150 and 400 bar on the quality of the obtained extracts and efficiency of the extraction was investigated. The highest extraction yield (3.43 %) was achieved by applying the extraction conditions of 400 bar and 60 °C. The analysis of the extracts was performed by gas chromatography and mass sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…It was considered that the chemical composition of A. ursinum is complex. The presence of about 100 compounds has been detected by various authors with different extraction methods and analytical methods of detection [ 6 , 14 , 20 , 21 , 22 ]. By comparing the results reported by different authors, it can be concluded that the chosen extraction technique and solvent significantly affect the profile of isolated compounds.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It was considered that the chemical composition of A. ursinum is complex. The presence of about 100 compounds has been detected by various authors with different extraction methods and analytical methods of detection [ 6 , 14 , 20 , 21 , 22 ]. By comparing the results reported by different authors, it can be concluded that the chosen extraction technique and solvent significantly affect the profile of isolated compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Additional differences may occur depending on the plant origin, vegetation period and used herbal parts. The antimicrobial activity of the Allium species is mainly attributed to various kinds of alk(en)yl alka/ene thiosulfinates and their transformation products [ 6 , 23 ] and polyphenolic compounds. Even the fresh A. ursinum is characterized by the presence of its characteristic odor from sulfur compounds such as allicin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this regard, new starches and other hydrocolloids have expanded the use and substitution of many ingredients [4], and traditional cereal flours have been replaced by other flours such as pulse flours [5] or nut flours [6,7]. New production methods include, for example, the use of critical CO 2 to conduct the extraction of different components [8] and the use of ultrasound assisted extraction or microwave assisted extraction [9,10]. From the point of view of consumers, studies have focused on consumers' attitudes towards organic products [11], gluten-free products [6], and the various kinds of innovations that result in the production of more natural or more sustainable foods [3,12].…”
mentioning
confidence: 99%